Outcomes of Single-Operator Cholangioscopy-Guided Lithotripsy in Patients with Difficult Biliary and Pancreatic Stones - Canena, Jorge (2018)
Background and Aims: Endoscopic retrograde cholangiopancreatography is the preferred strategy for the management of biliary and pancreatic duct stones. However, difficult stones occur, and electrohydraulic (EHL) and laser lithotripsy (LL) have emerged as treatment modalities for ductal clearance. Recently, single-operator cholangioscopy was introduced, permitting the routine use of these techniques. We aimed to evaluate the clinical effectiveness of cholangioscopy-guided lithotripsy using LL or EHL in patients with difficult biliary or pancreatic stones. Methods: This is a prospective clinical study – conducted at two affiliated university hospitals – of 17 consecutive patients with difficult biliary and pancreatic stones who underwent single-operator cholangioscopy-guided lithotripsy using two techniques: holmium laser lithotripsy (HL) or bipolar EHL. We analyzed complete ductal clearance as well as the impact of the location and number of stones on clinical success and evaluated the efficacy of the two techniques used for cholangioscopy-guided lithotripsy and procedural complications. Results: Twelve patients (70.6%) had stones in the common bile duct/common hepatic duct, 2 patients (17.6%) had a stone in the cystic stump, and 3 patients (17.6%) had stones in the pancreas. Sixteen patients (94.1%) were successfully managed in 1 session, and 1 patient (5.9%) achieved ductal clearance after 3 sessions including EHL, LL, and mechanical lithotripsy. Eleven patients were successfully submitted to HL in 1 session using a single laser fiber. Six patients were treated with EHL: 4 patients achieved ductal clearance in 1 session with a single fiber, 1 patient obtained successful fragmentation in 1 session using two fibers, and 1 patient did not achieve ductal clearance after using two fibers and was successfully treated with a single laser fiber in a subsequent session. Complications were mild and were encountered in 6/17 patients (35.2%), including fever (n = 3), pain (n = 1), and mild pancreatitis (n = 1). Conclusions: Cholangioscopy-guided lithotripsy using LL or EHL in patients with difficult biliary or pancreatic stones is highly effective with transient and minimal complications. There is a clear need to further compare EHL and HL in order to assess their role in the success of cholangioscopy-guided lithotripsy.